PELAKSANAAN ASESMEN KOMPETENSI MINIMUM PADA KEBIJAKAN MERDEKA BELAJAR DI SMA NEGERI 5 JENEPONTO - Andi Aco Agus; Irsyad Dahri; Sriwahyuni Sriwahyuni (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2022)
This study aims to determine (1). Stages of Implementation of Minimum Competency Assessment at SMA Negeri 5 Jeneponto (2) Obstacles encountered in the implementation of the Minimum Competency Assessment at SMA Negeri 5 Jeneponto. The approach used in this study is a qualitative approach using a descriptive type of research with data sources from school principals, teachers, and students (AKM participants). The data collection procedures used are observation (observation), interviews and documentation. The stages of research carried out are planning, implementation and writing stages of research results for drawing conclusions.The results of this study indicate that (1) The stages of implementing the Minimum Competency Assessment at SMA Negeri 5 Jeneponto are the preparation stage such as facilities (computer units, internet/wifi access, AKM guide books), holding workshops (training) for teachers, procurement proctor, conduct simulations and guidance for AKM participants. At the stage of the implementation process, there is supervision. As well as the evaluation and follow-up stages by getting used to reading before the lesson starts in order to improve students' reading literacy. (2) The obstacles faced in implementing the Minimum Competency Assessment at SMA Negeri 5 Jeneponto are the lack of teacher understanding, inadequate internet access, not all AKM participants can operate a computer, as well as the lack of interest of students in reading questions. As for the efforts made, namely, providing workshops (training) for teachers, dividing the implementation sessions for AKM participants, conducting simulations and supervision, and providing guidance or tutoring.